Transformations in the Catholic Ethical Theology - Ahmadreza Meftaah (اخلاق وحیانی)
The Christian ethical theology has undergone numerous transformations. The New Testament is considered to be the main origin of Christian ethics. The central theme of Jesus’s teachings was the kingdom of God and the transformation which was considered to be the prerequisite for being granted entrance into God’s kingdom. The ethics, as taught by Paul the Apostle, was based on virtues and it emphasized the internalization of ethical principles rather than the external moral orders and prohibitions. The ethical teachings of the Apostolic Fathers were mostly of preaching, pastoral, defensive, and instructive nature. For almost one thousand years there was no coherent and systematic science of ethics. Even Augustine, who greatly influenced the thoughts of the church by theorizing the concept of perpetual blessing, was not able to present a coherent ethical theology. Later, Thomas Aquinas presented the most systematic and detailed account of moral virtues and vices with a philosophical approach. However, ethical theology was still considered to be a part of theology, until after the Trent council and, particularly, by the influence of Alfonse Ligouri, the ethical theology was separated from doctrinal theology. When the “infallibility of the Pope” was approbated in the first council of the Vatican, the doctrinal authority of the church started interfering in the explanation of the ethical issues. In the contemporary era, and due to the advances in industry and medicine, new topics have arisen in the area of Catholic ethics.